The impact of climate change and sustainability standards on the insurance market - Sūda, Kiraṇa; Grima, Simon; Young, Peter C.; Özen, Ercan; Balusamy, Balamurugan
"The Impact of Climate Change and Sustainability Standards on the Insurance Market. The book explores the role of the insurance industry in contributing and responding to the harms that climate change has brought. This book delves into the physical and logical impacts, both direct and indirect, on the insurance industry. Subjects discussed include new technology such as big data, artificial intelligence, machine learning, the growth of sustainable economics with foreign direct investments (FDIs), trustworthiness, and ethics. Related use cases of data science for claim processing, fraud detection and prevention, policy administration, pricing, and underwriting are discussed along with cyber security issues, data protection, and big data regulatory reforms. To promote ESG sustainability, the insurance industry plays a critical and significant role. Climate-related risks are being factored into underwriting and investing strategies. Through their own operations and business activities, insurers may promote the ESG agenda and move towards sustainability. Also discussed are promoting diversity and inclusion, lowering greenhouse gas (GHG) emissions, resolving gender inequality, and helping communities through charitable work, which all improve a company's brand, reputation, and ESG credentials. The book is specially designed for administrators, lecturers, researchers, students of insurance and sustainability, students in financial services, insurance practitioners, actuaries, loss adjusters, underwriters, regulators, facilities management, utility companies, voluntary organizations, government departments, business leaders, policymakers, decision-makers, investors, risk managers, compliance managers, and audit managers amongst many others."--